Національно-культурна специфіка фразеологізмів з компонентом «голова» в українській, польській та англійській мовах - Гадзало, Анна (Видавництво Львівської політехніки, 2015)
This article is devoted to the national specifics of phraseological units containing component «head».In this research phraseological units are explored in lingvocultural aspect in comparable languages. The analysis was based on basis of phraseology material , which was extracted from Ukrainian, English, Polish language dictionaries.
Keywords: фразеологічна одиниця; національно-культурна специфіка; компонент «голова»